Evaluation of Clinical Profile and Hematological Parameters of Cases of Megaloblastic Anemia - Suthar, Hemang N; Shah, Tejas N (National Journal of Community Medicine, 2017)
Background: Megaloblastic anemia is not uncommon in India. In India, the most common cause of megaloblastic anemia is nutritional where as it is the pernicious anemia in Northern Europe. Aims and objectives: To study age and gender-wise distribution, diet patterns, clinical features and hematological parameters in patients with megaloblastic anemia. Material and methods: This was an observational cross-sectional study of the hundred patients of megaloblastic anemia. We included patients having anemia with MCV>100 fL, serum vitamin B12 level <250 pg/ml and/ or serum folic acid level<3 ng/ml with normal serum ferritin level were included. Detailed history, physical examination, laboratory parameters and radiological investigation were done. Results: Megaloblastic anemia is most common in age between 20-40 years of age. Male subjects were commonly affected. Most of the patients (69%) belong to lower socio-economic class. 50% patients had severe anemia (Hb<7 gm %). Cobalamin deficiency was responsible for megaloblastic anemia in the majority of patients. Conclusion: Megaloblastic anemia has wide clinical & hematological spectrum. The most common symptoms observed were a generalized weakness (98%), easy fatigability (96%), anorexia (64%) which is nonspecific, so high degree of suspicion is required to diagnose megaloblastic anemia.